Generation of employment potential in coffee-cardamom based cropping systems - HOSMANI, V S KORIKANTHIMATH, G M HIREMATH, M M (Journal of Spices and Aromatic Crops, 1999)
Studies carried out at Chettalli (Karnataka, India) on mixed cropping of coffee (Coffea robusta) with cardamom (Elettaria cardamomum) in comparison with mono cropping of coffee indicated greater potential of labour employment in mixed cropping system compared to mono cropping system. The mixed cropping system required 237 men and 710 women labourers per ha per year (9 years average) to carry out various operations which was 1.67 times higher than the mono cropping system. The correlation coefficient of yield and labour requirement in both mono and mixed cropping systems were high and significant.